Traditional Fields of Agricultural Economics, 1940s to 1970s. - Martin, Lee R. (Survey of Agricultural Economics Literature., 1973)
This is the second volume in the comprehensive three-volume work A Survey of Agricultural Economics Literature, published for the American Agricultural Economics Association. The general editor, Lee R. Martin, was a professor of agricultural economics at the University of Minnesota. The work will have wide use for reference, review, or study by students, agricultural economists, general economists, and other social scientists.